Relationship between palm oil price and soybean oil price / Noor Fatihah Rizal - Rizal, Noor Fatihah (Faculty of Plantation and Agrotechnology, 2019)
Palm oil is the major produced and traded oil in the world. However, the major challenges such as soybean oil are become the largest competitive oil as both of these products are substitute. Palm oil and soybean are two agricultures commodities which have many characteristics and are substitutable in many applications. When high in soybean oil price, the palm oil price also will follow suit. In the world traded there are more than 17 major oils and fats produced. . This paper investigates the price transmission in the world market for palm oil and soybean. The objective of this study is to determine the relationship between palm oil price and soybean price thus to determine the marketing strategy to make palm oil become dominant. By using the secondary annual data from year (1986-2016) for the variables, the relationship model been examined using two types of methods. Method of Ordinary Least Square (OLS) is used to see the relationship between palm oil price and soybean oil price and the result found it significant at one per cent level of significance. For the impulse response result, both variables are shows positive response toward each variable which palm oil has positive relationship to the soybean oil and vice versa. Overall, it can be concluded that there are many factors to stabilize the oil palm price. Several recommendations to increase the production and demand of palm oil such as producing high yielding material, improving in Research and Development (R&D), improve the RSPO management and continuous and increasing supply of palm oil in future. Next, there are few ways to control the substitution effects between soybean and palm oil such as price the palm oil fairly, increased quality of oil palm, make consumer know the benefits of palm oil and others.